Induction of RIPK3/MLKL-mediated necroptosis by Erigeron breviscapus injection exhibits potent antitumor effect - Guo, Xiuping; Li, Rui; Cui, Jinjin; Hu, Chujuan; Yu, Haoyang; Ren, Ling; Cheng, Yangyang; Jiang, Jiandong; Ding, Xiao; Wang, Lulu (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) is the second leading cause of tumor-related deaths worldwide. Resistance of tumor cells to drug-induced apoptosis highlights the need for safe and effective antitumor alternatives. Erigeron breviscapus (Dengzhanxixin in China) injection (EBI), extracted from the natural herb Erigeron breviscapus (Vant.) Hand.-Mazz (EHM), has been widely used in clinical practice for cardiovascular diseases. Recent studies have suggested that EBI’s main active ingredients exhibit potential antitumor effects. This study aims to explore the anti-CRC effect of EBI and elucidate the underlying mechanism. The anti-CRC effect of EBI was evaluated in vitro using CCK-8, flow cytometry, and transwell analysis, and in vivo through a xenograft mice model. RNA sequencing was utilized to compare the differentially expressed genes, and the proposed mechanism was verified through in vitro and in vivo experiments. Our study demonstrates that EBI significantly inhibits the proliferation of three human CRC cell lines and effectively suppresses the migration and invasion of SW620 cells. Moreover, in the SW620 xenograft mice model, EBI markedly retards tumor growth and lung metastasis. RNA-seq analysis revealed that EBI might exert antitumor effects by inducing necroptosis of tumor cells. Additionally, EBI activates the RIPK3/MLKL signaling pathway, a classical pathway of necroptosis, and greatly promotes the generation of intracellular ROS. Furthermore, the antitumor effect of EBI on SW620 is significantly alleviated after the pretreatment of GW806742X, the MLKL inhibitor. Our findings suggest that EBI is a safe and effective inducer of necroptosis for CRC treatment. Notably, necroptosis is a non-apoptotic programmed cell death pathway that can effectively circumvent resistance to apoptosis, which provides a novel approach for overcoming tumor drug resistance.